2014
DOI: 10.1016/j.jhealeco.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border health and productivity effects of alcohol policies

Abstract: This paper studies the cross-border health and productivity effects of alcohol taxes. We estimate the effect of a large cut in the Finnish alcohol tax on mortality, alcohol related illnesses and work absenteeism in Sweden. This tax cut led to large differences in the prices of alcoholic beverages between these two countries and to a considerable increase in cross-border shopping. The effect is identified using differences-indifferences strategy where changes in these outcomes in regions near the Finnish border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…In the context of alcohol-related mortality, Law and Marks (2019) examine the prohibition policies conducted in the United States between 1900 and 1920 with results suggesting the effectiveness of the policies. Johansson et al (2014), in contrast, did not find any mortality or alcohol-related health effects in Swedish regions near the Finnish border from alcohol tax cuts imposed in Finland. 1 Studies on less developed and former command economies add to the literature exploring relationships between alcohol policies, consumption, and the consequences in specific social and economic environments.…”
Section: Introductioncontrasting
confidence: 60%
“…In the context of alcohol-related mortality, Law and Marks (2019) examine the prohibition policies conducted in the United States between 1900 and 1920 with results suggesting the effectiveness of the policies. Johansson et al (2014), in contrast, did not find any mortality or alcohol-related health effects in Swedish regions near the Finnish border from alcohol tax cuts imposed in Finland. 1 Studies on less developed and former command economies add to the literature exploring relationships between alcohol policies, consumption, and the consequences in specific social and economic environments.…”
Section: Introductioncontrasting
confidence: 60%
“…Lovenheim and Slemrod (2010) is a notable exception in that it finds that one state's reduction in the minimum legal drinking age could lead to a substantial increase in teenage traffic fatalities in neighboring states. Likewise, Johansson et al (2014) find higher rates of workplace absenteeism in Sweden after a cut in Finnish alcohol taxes. What differentiates our work in this respect is the focus on an entire country (the United States) at the lowest level of geographic aggregation possible (counties) for a more dramatic change in alcohol policy (the repeal of federal prohibition).…”
mentioning
confidence: 92%
“…This paper investigates how the regulation of licensed hours at establishments that serve alcohol influences working hours, focusing primarily on worker absenteeism. While, there is no existing evidence along these lines, it has been previously demonstrated that other forms of alcohol legislation such as minimum drinking ages and reductions in alcohol taxation can influence workforce productivity (Carpenter and Dobkin, 2011a;Johansson et al, 2014). We use recent changes in legal pub and club (herein bars for simplicity) opening hours in the UK and Spain as 'quasi-natural' experiments to identify the effect of on-premise alcohol availability on absence.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of alcohol taxation, this idea has attracted some attention. For instance, Johansson, Pekkarinen and Verho () examine the effect of a cut in alcohol taxation in Finland which led to large differences in alcohol prices between Finland and Sweden. They show that this had a weak effect on mortality and alcohol related illnesses but increased workplace absenteeism, a 5% increase for males and a 13% increase for females in Swedish regions near the Finnish border when compared to Swedish regions that are over 100 km away from the border.…”
Section: Introductionmentioning
confidence: 99%